2018
DOI: 10.1029/2018ef000890
|View full text |Cite
|
Sign up to set email alerts
|

Satellite‐Observed Major Greening and Biomass Increase in South China Karst During Recent Decade

Abstract: Above-ground vegetation biomass is one of the major carbon sinks and provides both provisioning (e.g., forestry products) and regulating ecosystem services (by sequestering carbon). Continuing deforestation and climate change threaten this natural resource but can effectively be countered by national conservation policies. Here we present time series (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) derived from complementary satellite systems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(108 citation statements)
references
References 54 publications
8
100
0
Order By: Relevance
“…The LPDR data are posted to a consistent 25-km global Equal-Area Scalable Earth (EASE) Grid projection format (Armstrong & Brodzik, 1995). The current AMSR LPDR (version 2) has been used for a diverse set of science application studies, including quantifying the influence of vegetation and soil moisture conditions on SMAP FW retrievals (Du, Kimball, Galantowicz, et al, 2018), studying ecosystem water storage and phenology (Brandt et al, 2018;Tian et al, 2018), detecting vegetation isohydry/anisohydry behavior and resilience to drought (Anderegg et al, 2018;Li et al, 2017), and mapping paddy rice planting areas (Song et al, 2018).…”
Section: Study Domainmentioning
confidence: 99%
“…The LPDR data are posted to a consistent 25-km global Equal-Area Scalable Earth (EASE) Grid projection format (Armstrong & Brodzik, 1995). The current AMSR LPDR (version 2) has been used for a diverse set of science application studies, including quantifying the influence of vegetation and soil moisture conditions on SMAP FW retrievals (Du, Kimball, Galantowicz, et al, 2018), studying ecosystem water storage and phenology (Brandt et al, 2018;Tian et al, 2018), detecting vegetation isohydry/anisohydry behavior and resilience to drought (Anderegg et al, 2018;Li et al, 2017), and mapping paddy rice planting areas (Song et al, 2018).…”
Section: Study Domainmentioning
confidence: 99%
“…Previous studies have assessed the biomass in this region on small and large scales. For example, the largest biomass increase in the world occurred in the South China karst region between 1999 and 2012 [10]. Other studies reported the biomass in typical karst ecosystems, or along vegetation restoration areas based on surveys of small plots [2,6,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that conservation practices contributed significantly to increasing ABC during the period of project implementation. Finally, it was found that over 0.9 million km 2 of land in the region (75.3% of the land area) had, on-average, a 4% increase in biomass (Brandt et al 2018). Results from these studies appear to suggest that ecological engineering has contributed significantly to ecosystem recovery over much of the karst region.…”
Section: Ongoing Research Supporting Policy For Sustainable Karst Lanmentioning
confidence: 90%
“…Information from various sources indicate that the karst environment improved in the past 20 years (Zhang et al 2017). Specifically, a significant increase in aboveground biomass (on average C 4.0% over 0.9 million km 2 ) between 1999 and 2012 had occurred at the regional scale, which makes up approximately 5% of global areas with increasing biomass (Brandt et al 2018;Tong et al 2018). Aerial cover of KRD in southwestern China has decreased from 129,600 km 2 in 2006 (10.8% of the land area) to 100,700 km 2 in 2016 (8.4% of the land area).…”
Section: Introductionmentioning
confidence: 99%